2021
DOI: 10.3390/atmos13010071
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Generative Air Pollution Model with Variational Autoencoder and Environmental Factor Effect in Ulaanbaatar City

Abstract: Air pollution is one of the most pressing modern-day issues in cities around the world. However, most cities have adopted air quality measurement devices that only measure the past pollution levels without paying attention to the influencing factors. To obtain preliminary pollution information with regard to environmental factors, we developed a variational autoencoder and feedforward neural network-based embedded generative model to examine the relationship between air quality and the effects of environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…For more than 100 years, from 1881 to 1981, many experts such as Bil (Биль), Sorokin (Сорокин), and Grigiriev (Григириев) et al made contributions to the research. Finally, they concluded that the microorganisms of Koumiss, cow's milk fat-free fermented milk, and koji (assets) microorganisms of fermented milk drinks have common characteristics [13].…”
Section: Overview Of the Survey Research On Mongolian Koumiss Koji (A...mentioning
confidence: 99%
“…For more than 100 years, from 1881 to 1981, many experts such as Bil (Биль), Sorokin (Сорокин), and Grigiriev (Григириев) et al made contributions to the research. Finally, they concluded that the microorganisms of Koumiss, cow's milk fat-free fermented milk, and koji (assets) microorganisms of fermented milk drinks have common characteristics [13].…”
Section: Overview Of the Survey Research On Mongolian Koumiss Koji (A...mentioning
confidence: 99%